Effect of Nano-CSH and sodium sulfate on strength and durability of non-steam-curing high volume fly ash concrete. - Yongkang Du; Bitao Zhang; Dong Liu; Haoqian Wang; Yanyan Hu (PLoS ONE)
In this study, a novel nanomaterial early strength agent, CSH nano-crystal nucleus (NCSH), was used to compare with the conventional early strength agent, sodium sulfate (Na2SO4), to deal with the problem of insufficient early strength development of high volume fly ash concrete. The effects of NCSH, Na2SO4, and their combined action on the strength development, water absorption performance, and durability performance (impermeability, frost resistance, and carbonation) were investigated. The research results show that: the maximum strength of the concrete with Na2SO4 was only 12.9 MPa at 12 hours, which could not meet the requirement of demoulding. At 28 days, the strength had significantly decreased, and the larger the dosage, the more it had decreased. Using NCSH or a mix of NCSH and Na2SO4 allowed the concrete to attain the necessary strength for demoulding at 12 hours, and none of them showed any reduction at 28 days. The concrete durability test results show that: Na2SO4 decreased the impermeability, frost resistance and carbonation resistance of concrete, while NCSH improved above properties of concrete significantly, and the improvement of frost resistance and carbonation resistance when combined Na2SO4 and NCSH was not as good as that of NCSH alone. In addition, either NCSH or the combination of CSH and Na2SO4 could make the concrete reach the frost resistance level of F200, and the concrete with appropriate dose of NCSH can still maintain the low mass loss rate and high relative dynamic elastic modulus after 200 freeze-thaw cycles; while the concrete with Na2SO4 did not reach F200.